A polygeneration process for heat, power and DME production by integrating gasification with CHP plant: Modelling and simulation study. (December 2017) - Salman, Chaudhary Awais; Naqvi, Muhammad; Thorin, Eva; Yan, Jinyue
Abstract: Biofuels are a good substitute for the transport sector petroleum fuels to minimize carbon footprint and greenhouse gases emissions. Di-Methyl Ether (DME) is one such alternative with properties similar to liquefied petroleum gas but with lower SOx, NOx, and particulate emissions. In this work, a polygeneration process, integrating an existing combined heat and power (CHP) plant with biomass gasification to synthesize DME, is proposed and modelled. Process integration is based on a hypothesis that the CHP plant provides the necessary heat to run the co-located gasification plant for DME synthesis and the waste heat from the gasification process is recovered and transferred to the CHP plant. The feed for gasification is taken as refuse derived fuel (RDF) instead of conventional wood derived biomass. The process integration leads to higher overall combined efficiency (up to 71%) which is greater than stand-alone efficiencies (up to 63%) but lower than stand-alone CHP plant efficiency (73.2%). The further technical evaluation shows that the efficiency of the polygeneration process is depends heavily on the gasifier capacity integrated with the existing CHP plant and also on the conversion route selected for DME synthesis i.e. recycling of unconverted syngas to the DME reactor or transferring it to the boiler of the CHP plant. The simulation results also indicate that once-through conversion yields less DME than recycling, but at the same time, once-through conversion affects the district heat and electric power production of the CHP plant lesser than by using the recycling route.